Detection of extended spectrum β-lactamase in Pseudomonas spp. isolated from two tertiary care hospitals in Bangladesh - Begum, Shahanara; Salam, Md. Abdus; Alam, Kh Faisal; Begum, Nurjahan; Hassan, Pervez; Haq, Jalaluddin Ashraful (BioMed Central, 2013)
Background: Extended spectrum ß-lactamases (ESBLs) represent a major group of lactamases responsible for resistance, mostly produced by gram-negative bacteria, to newer generations of ß-lactam drugs currently being identified in large numbers worldwide. The present study was undertaken to see the frequency of ESBL producing Pseudomonas spp. isolated from six hundred clinical specimens (wound, pus, aural, urine, sputum, throat and other swabs) collected over a period of three years from two tertiary care hospitals in Bangladesh. Findings: Aerobic bacterial culture was performed on aseptically collected swabs and only growth of Pseudomonas was considered for further species identification and ESBL production along with serotyping of Pseudomonas aeruginosa. Antimicrobial susceptibility testing was carried out using the Kirby-Bauer agar diffusion method and ESBL production was detected on Mueller Hinton agar by double-disk synergy technique using Amoxicillin-Clavulanic acid with Ceftazidime, Cefotaxime, Ceftriaxone and Aztreonam. Culture yielded 120 Pseudomonas spp. and 82 of them were biochemically characterized for species. Pseudomonas aeruginosa was found to be the predominant (90.2%) species. Of 82 isolates tested for ESBL, 31 (37.8%) were ESBL positive with 29 (93.5%) as Pseudomonas aeruginosa, the remaining 2 (6.5%) were Stenotrophomonas maltophilia and Ralstonia pickettii. Antibiogram revealed Imipenem as the most effective drug (93.3%) among all antimicrobials used against Pseudomonas spp. followed by Aminoglycosides (63.7%). Conclusion: ESBL producing Pseudomonas spp. was found to be a frequent isolate from two tertiary care hospitals in Bangladesh, showing limited susceptibility to antimicrobials and decreased susceptibility to Imipenem in particular, which is a matter of great concern.